FRI0127 Angiogenic Placental Factors during Pregnancy in Rheumatoid Arthritis. (15th July 2016) - Förger, F.; Baumann, M.; Risch, L.; Raio, L.; Surbek, D.; Wiedemann, U.; Zbinden, A.
Abstract : Background: Reduced birth weight in infants born to women with rheumatoid arthritis (RA) is often related to active maternal disease during pregnancy. Objectives: We hypothesized that RA might have an influence on placental function and investigated whether pro-angiogenic and anti-angiogenic placental proteins such as placental growths factors (PLGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) were differently regulated in patients with RA compared to healthy controls. Methods: Sera of 27 pregnancies in RA patients and of 10 aged-matched healthy women were analyzed for PLGF and sFLT-1 by ELISA once at each trimester (gestational week 10–12, 20–22 and 30–32). Disease activity of all RA patients was measured by DAS28-CRP and CRP. Neonatal birth weights and birth weight percentiles were correlated with PLGF- and sFLT-1- levels. Results: Of the 37 pregnancies there was no case of preeclampsia, neither in the group of RA patients nor in the group of healthy controls. Median birth weight of the newborns from RA patients was 2890 g (range 1250–4000). Among all pregnancies of RA patients, the levels of PLGF and sFLT-1 were similar in active and inactive disease. At the third trimester of pregnancy, RA patients showed lower levels of the pro-angiogenic placental protein PLGF than healthy controls (P=0.021). By contrast, levels of the anti-angiogenic protein sFLT-1 did not differ between RA patients and healthy women. The sFLT-1/PLGF ratio was lower in healthy women than in RA patients (P=0.021). Moreover the sFLT-1/PLGF ratio showed a negative correlation with the birth weight percentile. Conclusions: RA patients showed reduced levels of the pro-angiogenic placental protein PLGF which might reflect a dysfunction of the placenta with an effect on birth weight in this disease. Disclosure of Interest: None declared